THE EFFECT OF STORY MAPS STRATEGY ON READING COMPREHENSION NARRATIVE TEXT IN ENGLISH DEPARTMENT STUDENTS - Nurchurifiani, Eva; Febriyanti, Febriyanti (JETA (Journal of English Teaching and Applied Linguistic), 2021)
The research was conducted in seventh semester students of Prose Course English Department of STKIP PGRI Bandar Lampung. The objective of this research is to know whether there is the influence of story maps strategy towards students’ reading comprehension in narrative text. The samples of this research was two classes. The first class was VII (A) as the experimental class and the second class was VII (B) as the control class. The experimental class consisted of 32 students and the control class consisted of 32 students. In this research, the researcher used experimental method. In collecting the data, the researcher used reading test with the form of multiple choice and consist of four options. Based on the data analysis, the value of t-test is 6,41 and t-table is 2,66. It means that t-test is higher than t-table (6,41>2,66) in significant level 0,05. So, the null hypothesis (Ho) is rejected and hypothesis alternative (HI) is accepted. Finally, the researcher concluded that there is a significant influence of teaching reading comprehension in narrative text through Story Maps Strategy in English department students of STKIP PGRI Bandar Lampung in academic year 2018/2019.